2011
DOI: 10.3350/kjhep.2011.17.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum HBsAg-to-HBV DNA ratio predicts a virologic response to entecavir in chronic hepatitis B

Abstract: Background/AimsDecay of hepatitis B surface antigen (HBsAg) titers has previously been shown to be predictive of a virologic response (VR), especially during peginterferon-alpha therapy. However, the role of HBsAg levels in predicting a VR to nucleos(t)ide analog therapy has not yet been established. In this study we sought to determine whether the VR can be predicted from HBsAg titers in nucleos(t)ide-naïve chronic hepatitis B (CHB) patients treated with entecavir.MethodsCHB patients who started entecavir as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…26 Another paper reported that HBeAgnegative patients usually had a longer HBV infection history, and were expected to have more extensive HBV DNA integration, compared with HBeAg-positive patients. 27 While the serum HBsAg to HBV DNA ratio in patients not achieving HBsAg seroclearance in our study (0.58) was similar to that observed by others (0.5-0.6), it was significantly lower in patients achieving HBsAg seroclearance (0.35). This may be due to enhanced host immunity in relation to the control of subviral production, or because fewer HBV integration events occurred in patients achieving HBsAg seroclearance than in those not achieving HBsAg seroclearance, as the proportion of HBeAg negative patients was significantly higher in the latter group, in our study.…”
Section: Discussionsupporting
confidence: 90%
“…26 Another paper reported that HBeAgnegative patients usually had a longer HBV infection history, and were expected to have more extensive HBV DNA integration, compared with HBeAg-positive patients. 27 While the serum HBsAg to HBV DNA ratio in patients not achieving HBsAg seroclearance in our study (0.58) was similar to that observed by others (0.5-0.6), it was significantly lower in patients achieving HBsAg seroclearance (0.35). This may be due to enhanced host immunity in relation to the control of subviral production, or because fewer HBV integration events occurred in patients achieving HBsAg seroclearance than in those not achieving HBsAg seroclearance, as the proportion of HBeAg negative patients was significantly higher in the latter group, in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In three previous ETV studies no baseline factor predictive of HBeAg loss or HBeAg seroconversion could be identified [24,26,29]; however, in another ETV study, baseline qHBsAg was a predictor of HBeAg loss/ seroconversion in HBeAg-positive patients after 24 months of ETV treatment [25]. In a previous study with lamivudine, elevated baseline ALT was found to be a significant predictor of HBeAg loss or HBsAg loss [43].…”
Section: Discussionmentioning
confidence: 92%
“…In interferona-based anti-HBV therapy, an on-treatment decline in qHBsAg has been shown to be a predictor of a sustained virological suppression and HBsAg clearance in HBeAg-positive and HBeAg-negative patients [10,20,23]. With nucleoside/nucleotide analogue (NUC) HBV therapy, the clinical utility of qHBsAg as a potential predictor of response to treatment remains unclear [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Confirming immune control over viral replication was the first step of immune clearance. This ratio has been shown to be higher during the low-replicative phase, compared to immune-tolerant, immune-clearance and HBeAg negative hepatitis phase and to be repeatable regardless to ethnicity or genotype [ 19 - 21 ]. Nevertheless, in our study, the HBsAg / HBV DNA ratio was higher in samples with low HBV DNA values than in those with high HBV DNA values, as reported by others [ 22 ].…”
Section: Discussionmentioning
confidence: 99%